Regulatory Dossier Submission In India - Gupta, Apeksha; Rai, Shivaji (Asian Journal of Pharmaceutical Research and Development, 2015)
Drug Regulatory Authority is defined as an authority appointed by the government to administer the granting of marketing authorization/approval of pharmaceutical products and biologicals in a country. It is also called as the Licensing Authority or Marketing Authority. The Drug Regulatory Authority of India is the Central Drugs Standard Control Organization (CDSCO), under the Ministry of Health and Family Welfare (MOHFW). Pharmaceutical Dossier of India is the major document required for the process of marketing approval of the pharmaceutical products and biologicals in India. Its content and format follows the Common Technical Document (CTD) as set out by the International Conference on Harmonization (ICH). The CTD of India is organized into 5 Modules. The information required under each module is suitably detailed in this article